Recognition Awards in Pathology Specialty Societies: Gender Analysis Among Physician Recipients. Issue 4 (6th August 2022) - Wobker, Sara E; Ginter, Paula S; Parra-Herran, Carlos; Schwartz, Lauren E; Booth, Garrett S; Fitzhugh, Valerie A; Silver, Julie K; Khani, Francesca
Abstract: Objectives: Recognition awards build physician reputation and facilitate career advancement. We hypothesize women physicians are underrepresented as award recipients by pathology medical societies compared with representation in the specialty. Methods: We analyzed publicly available online information about physician recipients (January 2015 to December 2021) from three general pathology society websites. Recipient gender was determined by pronoun use, first name, and photograph. Representation was compared with Association of American Medical Colleges (AAMC) specialty data from 2015 and 2019, which showed a minimum of 36.7% women pathologists in 2015 and up to 43.4% in 2019. Results: Twenty-six awards and 230 physician recipients were included in the analysis. A total of 159 (69.1%) men physicians and 71 (30.9%) women physicians received awards. Overall, women physicians were underrepresented in recognition awards compared with AAMC benchmarks. Prestigious awards (defined as those that recognize a person's body of work over time) showed a similar disparity with 22 (30.1%) of 73 recipients being women. Men physicians were more likely to receive multiple awards. Conclusions: Women physicians are underrepresented overall for recognition awards by pathology medical societies. Disparities are greater for prestigious awards. Further research is needed to better understand the reasons for these findings and how they affect women physicians' careers.